Porous Aggregate from Coal Mining Waste and Development Light Weight Concrete Based on It - Turgunovich, Shakirov Tuigunzhon; Kizi, Muminova Nilufar Abdulla (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to determining the optimal composition of the charge for the production of artificial porous aggregate from coal mining waste and bentonite clays, which are considered local raw materials for the development of new generations of thermal insulation and ultra-lightweight and structurally strong concrete. When developing the optimal composition of the charge for the production of porous aggregates from mineral rocks and coal mining waste, a method was used that was used as the basic theory for the production of expanded clay.